How Calcifications Guide the Diagnosis: A Case of Gorlin's Cyst - Rym Kammoun; Manel Gharbi; Rawia Jaziri; Nawress Ghadhab; Imen Chaabani; Touhami Ben Alaya (Clinical Case Reports)
ABSTRACT Calcified odontogenic epithelial cyst known as Gorlin's cyst is one of the benign odontogenic tumors of the maxillae. In imaging, the most revealing aspect is a well‐limited osteolytic image with peripheral calcifications. The aim of the study was to highlight these radiological features to establish the correct diagnosis and appropriate treatment.